Research on the Construction and Practice of Online-Offline Blended Teaching Mode in College English for Art Students Based on the POA Approach - Xiao, Qiong; Yue, Ting (Pacific International Journal, 2024)
The Production-Oriented Approach (POA) is a foreign language teaching theory with Chinese characteristics proposed by Professor Wen Qiufang's team at the China Foreign Language Education Research Center of Beijing Foreign Studies University. Based on the "Output Hypothesis", this theory emphasizes that the purpose of language learning is for effective output. In the context of rapid information technology development, this study applied the POA Approach as the theoretical foundation and uses the Online-Offline Blended Teaching Mode in college English courses for artistic majors. After a 16-week experiment, data were collected through tests, questionnaires, and interviews to analyze the application effect of the POA-guided online-offline blended teaching mode for college English among undergraduate art students in ordinary universities. The results showed that this mode effectively improved students final grades and received high recognition from students, particularly in terms of online teaching and targeted explanations provided by teachers. This mode successfully stimulated students learning enthusiasm and significantly enhanced classroom teaching effectiveness and course quality.